Pelaksanaan Jual Beli Bahan Bakar Minyak Melalui Pertamini di Kecamatan Denpasar Utara - Putu Angelita Putri; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2024)
Nowadays, people have created creative ideas resembling the machinery at PT Pertamina to make profits with the uneven distribution of fuel oil by creating Pertamini. Pertamini traders are unlicensed traders who prey on unsuspecting customers by selling substandard fuel at inflated prices. This is very contrary to consumer rights. The problems are, How the factors that cause consumers to prefer Pertamini in North Denpasar Subdistrict? and How is the responsibility of fuel oil traders through Pertamini for consumers who are harmed in North Denpasar Subdistrict? This research uses empirical methods with sociological, conceptual and statutory approaches. The research location was carried out in North Denpasar District. Related data collected in this study using primary data and secondary data. Therefore, the researcher concludes that the factors that cause consumers to choose to fill fuel oil in Pertamini are in addition to consumers following the latest technological trends, as well as the advantages of Pertamini, including faster and more practical use. Then, consumers who are disadvantaged regarding the price given through Pertamini are more expensive and the dose given is not in accordance with what should be obtained. Therefore, pertamini traders can be held accountable for the losses suffered by the consumers themselves.